2000
DOI: 10.1093/ndt/15.6.862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of icodextrin in automated peritoneal dialysis on blood pressure and bioelectrical impedance analysis

Abstract: Use of icodextrin for the daytime dwell in APD results in improved fluid balance and blood pressure control compared with 2.27% glucose. MFBIA detected clinically important changes in fluid content in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 20 publications
2
74
1
Order By: Relevance
“…The lack of influence of improved ultrafiltration on BP control in this study is on the surface disappointing and differs from the findings of uncontrolled studies (18,21,22). It should be noted, however, that achieved BP control throughout the study in both patient groups was very satisfactory, reflecting both a good quality of care by participating physicians and the freedom to use drug therapy as required in the study protocol.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The lack of influence of improved ultrafiltration on BP control in this study is on the surface disappointing and differs from the findings of uncontrolled studies (18,21,22). It should be noted, however, that achieved BP control throughout the study in both patient groups was very satisfactory, reflecting both a good quality of care by participating physicians and the freedom to use drug therapy as required in the study protocol.…”
Section: Discussioncontrasting
confidence: 92%
“…We found that when icodextrin is used during the long exchange compared with 2.27% glucose, ultrafiltration is better preserved and a sustained reduction in weight, primarily attributable to changes in the ECF, occurs. This supports the changes in weight observed in a recent randomized study (17) and in uncontrolled studies of manipulation of fluid status in PD patients, although in these reports, the changes in BP were greater (18,21,22). Furthermore, this change does not appear to have a detrimental effect of residual urine volume.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is becoming increasingly clear that one of the primary responsibilities of clinicians in the management of PD patients is the balance between adequate control of fluid status and preservation of residual renal function. Numerous clinical studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(35)(36)(37) and more than 9 years of post-marketing surveillance have confirmed that icodextrin is a safe and well-tolerated osmotic alternative PD solution to glucose. The most significant adverse effect reported to date is a cutaneous hypersensitivity reaction (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…As the sieving coefficient for sodium is about 0.6, i.e., that less sodium than water is removed with hypertonic exchanges that are glucose based (21), it may be posited that the efficacy of ultrafiltration in normalizing sodium/volume status is limited. It is noteworthy that when a glucose polymer (icodextrin) is used in place of glucose, a set of pores with larger mean radius is engaged (22) to move sodium and water into the peritoneal space and that there is no membrane restriction to sodium transport (23). Sodium then sieves at 1.0 as ultrafiltrate and plasma water carry identical sodium concentrations.…”
Section: Editorialmentioning
confidence: 99%